Combinatorial and global optimization - Pardalos, P. M. (Panos M.), 1954-; Migdalas, Athanasios; Burkard, Rainer E. (Series on applied mathematics ;, 2002)
Annotation Combinatorial and global optimization problems appear in a wide range of applications in operations research, engineering, biological science, and computer science.